Thursday

April 17, 2014

April 17, 2014

Posted by **Julie** on Sunday, September 28, 2008 at 4:28pm.

- newton's method -
**Damon**, Sunday, September 28, 2008 at 6:56pmg(x) = f(x)-R

look for zero of g(x)

Xn+1 = Xn -g(Xn)/g'(Xn)

here we have

Xn+1 = Xn -(f(Xn)-R)/f'(Xn)

Xn+1 =Xn -f(Xn)/f'(Xn) + R/f'(Xn)

so here

f(x)/f'(x) = cos x sin x

R/f'(x) = - R x cos^2 x

so

f' = 1/(x cos^2x)

f = cos x sin x * 1/(x cos^2 x) = sin x/x cos x

I am not sure I have all your parentheses right and it does not quite check out but that is the idea.

**Related Questions**

newton's method #2 - i want to verify that when newton's method is used to ...

math - The sequence x_1, x_2, x_3, . . ., has the property that x_n = x_{n - 1...

math - repost - The sequence x_1, x_2, x_3, . . ., has the property that x_n = ...

math - how to find the reciprocal?? you flip the reciprocal example (4 over 5 ...

math - what is the solution 7x + 5 - 3x > -15 a.x_> -5 b. x_<-5 c.x_&...

Matrix - How do you solve for this matrix. X*X^t=0? What matrix times its ...

algebra - When i have a matrix 4 X 4 and i have to multiply it by a 4 X 3 i know...

Math - Let p>q>0 with p+q = 1 and a = q/p < 1. Let X_n denote the ...

math - Show that if x is a nonzero column vector in R^n, then the nxn matrix: A...

algebra 2! - Given f(X)=the square root of x-2 and g(x_=6/x-3 (+1), write the ...